Nomophobia Among Health Care Providers: A Prevalence and Association Study (Bangladesh Journal of Medical Science, 2026)
Background smart phones devices have become utilized in our daily life and it is now a common practice especially in the medical field. Nomophobia or -No Mobile PHOBIA- which is the fear of feeling uncomfortable without a cell phone is one of the negative aspects of mobile phones that has illustrated a massive increase over the past years. Aim Assess the prevalence of nomophobia among health acre providers and assess its relation to mental health as well as self-esteem. Methods 137 participants were assessed for nomophobia level using nomophobia questionnaire as well as self-esteem and mental health, as well as their sociodemographic characters, the correlation between nomophobia level and different factors was assessed. Results All the participants involved in the study (n=137) had nomophobia 100%, most of the participants had moderate nomophobia 59.85% (n=82) and 16.79% (n=23) had severe nomophobia and 23.36% (n=32) had mild nomophobia, there was a significant weak negative correlation between nomophobia level and self-esteem as well as mental health. Conclusion Nomophobia is a prevalent contemporary health concern that requires immediate care and management approaches.BJMS, Vol. 25 No. 01 January’26 Page : 163-168